Effect of music therapy on nursing students' first objective structured clinical exams, anxiety levels and vital signs: A randomized controlled study - GÜNDÜZ, CEYDA SU (CHURCHILL LIVINGSTONE, 2021)
Background: Music is a tool that can be used to reduce stress and anxiety, maintain vital signs at normal levels, and increase exam success. Objectives: This study aimed to determine the effect of music therapy on nursing students' first objective structured clinical exam success, anxiety levels, and vital signs, and to reveal their views about music therapy in the context of an exam. Design: Mixed-pattern single-blind randomized controlled qualitative study. Setting: Department of Nursing, Faculty of Health Sciences, Ankara, Turkey. Participants: First-year students enrolled in the Fundamentals of Nursing II course were randomly assigned to an experimental (n = 61) or control group (n = 64). Twenty-two (22) experimental group students provided the sample for the qualitative stage. Methods: Data were collected between February and June 2018 using the Informative Features Form, State-trait Anxiety Inventory, Vital Signs Assessment Form, Skill Checklists, and Focus-group Interview Form. All students completed the theoretical classes, laboratory classes, and small-group studies. The experimental group participated in five music therapy sessions two weeks before the exam. All students' vital signs were measured before and after the exam. Three focus group interviews were conducted with the 22 experimental group students in the week after the exam. Results: The blood pressure values of the experimental group before and after the exam were significantly lower than those of the control group (p < 0.05). No significant difference was observed between exam success and anxiety levels between the two groups. In the focus group interviews, students said they found music therapy suitable for reducing anxiety in their daily lives, but not before the exam. Conclusions: Music therapy had positive effects on the students' blood pressure but had no effect on exam success or anxiety levels. This study suggests that more music therapy sessions be conducted with different groups of students in greater numbers before different exams.
Keywords: Music therapy; Anxiety; Vital signs; Nursing students; Objective structured clinical exam; OSCE; EXAMINERS